Küreselleşme Ve Küresel Markalaşma: Yerellik Ve Kültürel Göstergeler Bağlamında Pringles Örneği - Kınay, Ömür (The Turkish Online Journal of Design, Art and Communication, 2013)
It is no argument that the world has become an increasingly interactive place. This is an obvious result of globalization. In direct parallel to this, different brands have adapted their advertising strategies wherein they produced advertisements for particular countries, coded with images of their particular culture. The type of products the producers put forward and the way these products are presented to consumers in regards of cultural codes will be evaluated. This study will take into consideration a particular product of the brand Pringles, which is a globally well-known brand, and is sold all around the United Kingdom, is being analyzed. The product called Kebap the package design will be examined according to Roland Barthes’s semiotic methodology, in the light of globalization and localization.
Keywords: Globalization; Branding; Culture; Semiology; Küreselleşme; Markalaşma; Kültür; Göstergebilim